Keanekaragaman Coccinellidae Predator Pada Beberapa Ekosistem Perkebunan di Kabupaten Dharmasraya - Efendi, Siska Chiko; Yaherwandi, Yaherwandi; Noferta, Ade; Muhammad, Aditya (Biosfer: Jurnal Tadris Biologi, 2019)
The objectives of this research were to study the species diversity and to determine the dominant species of lady bird beetle predators in high land plantation ecosystem in West Sumatera. The samples were taken by hand collection and sweep net. The data of species diversity were analyzed using Shannon-Wiener index, evenness of species were analyzed by Simpson index, and  dominant species using important value index. The results showed that there were 91 individuals predator found which consisted of 7 species. The highest  species diversity (1.74) and evenness (0.89) were found in Pulau Punjung. The lowest diversity and evennes (1,40) and (0,75) was found in Koto Besar. The highest  species importance value index was 1,00, that was Menochillus sexmaculatus.